Tornar-se pai na adolescência: vivências e representações - Bonalume, Bruna Carolina [UNESP] (2014)
Issues related to sexuality and to reproductive and sexual health of adolescents is a main concern of many social sectors. Among the studies on youth, teen pregnancy has been privileged, often revealing speeches guided by punitive and prejudicial perceptions, which are associated with irresponsibility and exposure to risks. The discussions focus almost solely on women, with less or no focus on fatherhood. Thus, there is a forgetfulness of the teenage man, who most often doesn’t find his place together with public policies, especially when it comes to teen pregnancy. Thereby, this study aims to understand the social representations about the paternity process and to grasp the meanings and experiences set forth in this process. The survey was conducted with 17 adolescents from 9 to 18 years old, residents of a suburb in the municipality of São Manuel - SP. According to the object of study, the Social Representations were adopted as the theoretical framework, and the qualitative research as a methodological resource, together with a semi-structured interview. At the end of the collection, the interviews were transcribed and subjected to the content analysis technique of Bardin. From this technique, three core categories were identified: the discovery of pregnancy, difficulties and changes experienced by adolescents when becoming fathers and the meaning of fatherhood. After analyzing the data, it was found that the experience of fatherhood has brought significant changes in the lives of these adolescents in economic, emotional, personal and social terms. It is noteworthy that this experience has generated feelings of satisfaction to overcome the function of being just a provider father, which is shown by caring for their child and primarily through emotional relationships between them